Work values across generations: Development of the New Work Values Scale (NWVS) and examination of generational differences - Stiglbauer, Barbara; Penz, Marlene; Batinic, Bernad (Frontiers in Psychology, 2022)
The “battle for talent” requires organizations to more strongly focus on employer branding strategies, and, thus, on work values or work orientations of potential candidates. We therefore developed and validated the New Work Values Scale (Study 1; n = 316), a brief, 28-item, rating scale that covers a broad set of both, instrumental and symbolic, values, relevant for the appraisal of an employers’ attractiveness. We also applied the scale to a sample representative to the German online population, to explore the controversially discussed generational differences in work values (Study 2; n = 956). Results revealed that work values associated with sustainable organizational development or basic needs were highly similar across generations. Younger and older generations only differed significantly with regard to how much they valued clarity, money, career, development, stimulation, and relating, all of which are highly plausible from a lifecycle perspective.